Presenting Characteristics, Treatment Patterns, and Outcomes among Patients with Venous Thromboembolism during Hospitalization for COVID-19 - Fernández-Capitán, Carmen; Barba, Raquel; Díaz-Pedroche, María del Carmen; Sigüenza, Patricia; Demelo-Rodriguez, Pablo; Siniscalchi, Carmine; Pedrajas, José María; Farfán-Sedano, Ana I.; Olivera, Pavel Eduardo; Gómez-Cuervo, Covadonga; Llamas, Pilar; Villares, Paula; Sanchez, Olivier; López-Reyes, Raquel; Catella, Judith; Bikdeli, Behnood; Weinberg, Ido; Tafur, Alfonso J.; Jiménez, David; Monreal, Manuel (Seminars in Thrombosis and Hemostasis, 2020)
Venous thromboembolism (VTE) is common in patients with coronavirus disease-2019 (COVID-19). However, limited data exist on patient characteristics, treatments, and outcomes. To describe the clinical characteristics, treatment patterns, and short-term outcomes of patients diagnosed with VTE during hospitalization for COVID-19. This is a prospective multinational study of patients with incident VTE during the course of hospitalization for COVID-19. Data were obtained from the Registro Informatizado de la Enfermedad TromboEmbólica (RIETE) registry. All-cause mortality, VTE recurrences, and major bleeding during the first 10 days were separately investigated for patients in hospital wards versus those in intensive care units (ICUs). As of May 03, 2020, a total number of 455 patients were diagnosed with VTE (83% pulmonary embolism, 17% isolated deep vein thrombosis) during their hospital stay; 71% were male, the median age was 65 (interquartile range, 55–74) years. Most patients (68%) were hospitalized in medical wards, and 145 in ICUs. Three hundred and seventeen (88%; 95% confidence interval [CI]: 84–91%) patients were receiving thromboprophylaxis at the time of VTE diagnosis. Most patients (88%) received therapeutic low-molecular-weight heparin, and 15 (3.6%) received reperfusion therapies. Among 420 patients with complete 10-day follow-up, 51 (12%; 95% CI: 9.3–15%) died, no patient recurred, and 12 (2.9%; 95% CI: 1.6–4.8%) experienced major bleeding. The 10-day mortality rate was 9.1% (95% CI: 6.1–13%) among patients in hospital wards and 19% (95% CI: 13–26%) among those in ICUs. This study provides characteristics and early outcomes of patients diagnosed with acute VTE during hospitalization for COVID-19. Additional studies are needed to identify the optimal strategies to prevent VTE and to mitigate adverse outcomes associated.
Keywords: COVID-19; venous thromboembolism; hospitalization; outcomes